Choosing two business degrees versus choosing one: What does it tell about mutual fund managers' investment behavior? - Laura Andreu; Alexander Pütz (University of Cologne, Centre for Financial Research (CFR), 2016)
We analyze what a second business degree reveals about the investment behavior of mutual fund managers. Specifically, we compare investment risk and style of managers with both a CFA designation and an MBA degree to managers with only one of these qualifications. We document that managers with both degrees take less risk, follow less extreme investment styles, and achieve less extreme performance outcomes. Our results are consistent with the explanation that managers with a certain personal attitude that makes them take less risk and invest more conventionally choose to gather both qualifications. We rule out several alternative explanations: our results are not driven by the respective contents of the MBA and the CFA program, by the manager's skill, or by the fund family's investment policy.
Keywords: G23; 330; Mutual funds; Investment behavior; Manager education; MBA; CFA